No emotion is an island: an overview of theoretical perspectives and narrative research on emotions in sport and physical activity. Issue 2 (15th March 2017) - Tamminen, Katherine A.; Bennett, Erica V.
Abstract: Within sport and physical activity settings emotions have typically been conceived and explored from an individualistic or intrapersonal perspective, although researchers are increasingly turning their attention to the interpersonal aspects of emotions and emotion regulation. In this paper, we provide a theoretical overview of the social or interpersonal aspects of emotions from a psychological perspective, and we also consider theoretical perspectives of emotion as intersubjective, social, performative and embodied. We then provide a review of narrative research on emotion in sport and physical activity contexts and provide suggestions for future research in this area. We suggest that narrative approaches can advance research on emotions in sport and physical activity by exploring how emotions arise within the context of social relationships; by exploring how emotional stories or narratives function and are used by athletes, coaches, and others within sport and physical activity contexts; by examining how emotions are created, recreated, and sustained through the stories people tell; by examining how collective and group-based emotions are intertwined with one's identity and identity development; and by highlighting the ways in which social and cultural narratives within sport shape athletes' emotional experiences. We conclude by describing some challenges we have faced in conducting qualitative research from a narrative lens, and we describe how we have navigated these issues as a way of offering some 'lessons learned' from our own research.